Five new species and numerous locality records of Spirobolida millipedes from Madagascar (Diplopoda, Spirobolida, Pachybolidae) - Wesener, Thomas (Zootaxa, 2024)
Based mainly on the results of generalized American biodiversity inventory programmes, several samples of Malagasy Spirobolida millipedes became available to study. Based on this material, five new species of Spirobolida are described from Madagascar: four potential microendemic species, Aphistogoniulus amberivery sp. nov. from the Amberivery forest, A. manombo sp. nov., from the lowland rainforest of Manombo, Spiromimus endemicus sp. nov. from the Montagne des Français, and a species from the littoral forest of Tampolo, tentatively placed in the genus Eucarlia Brölemann, 1913, E. tampolo sp. nov.. A fifth species appears to be more widespread and is a morphologically unusual species of the genus Alluviobolus Wesener, 2009, A. omega sp. nov.. Aphistogoniulus manombo sp. nov. was previously described as a population of A. jeekeli Decker & Wesener, 2011. One of the most enigmatic Malagasy millipede species, Spirobolus olympiacus Karsch, 1881, is redescribed based on topotypic material as Colossobolus olympiacus (Karsch, 1881) new combination. Additional locality data is provided for 14 other Spirobolida species, of which 11 are listed on the IUCN Red List: Aphistogoniulus aridus Wesener, 2009, A. diabolicus Wesener, 2009, A. erythrocephalus (Pocock, 1893), A. hova (de Saussure & Zehntner, 1897), Colossobolus semicyclus Wesener, 2009, Spiromimus albipes Wesener & Enghoff, 2009, S. litoralis Wesener & Enghoff, 2009, S. simplex Wesener & Enghoff, 2009, S. triaureus Wesener & Enghoff, 2009, S. univirgatus deSaussure & Zehntner, 1901, Flagellobolus pauliani Wesener, 2009, Dactylobolus bivirgatus (Karsch, 1881), Madabolus maximus Wesener & Enghoff, 2008 and Hylekobolus rufus Wesener, 2009. Fourteen new genetic barcoding COI sequences are provided for nine species: Hylekobolus rufus, Colossobolus semicyclus, Aphistogoniulus amberivery sp. nov., A. aridus, A. diabolicus, A. erythrocephalus, A. hova, Spiromimus univirgatus and S. scapularis Wesener & Enghoff, 2009.